Comprehensiveness of HIV care provided at global HIV treatment sites in the IeDEA consortium: 2009 and 2014. Issue 1 (1st January 2017) - Fritz, Cristin Q; Blevins, Meridith; Lindegren, Mary Lou; Wools‐Kaloutsian, Kara; Musick, Beverly S; Cornell, Morna; Goodwin, Kelly; Addison, Dianne; Dusingize, Jean Claude; Messou, Eugène; Poda, Armel; Duda, Stephany N; et al.
ABSTRACT: Introduction: An important determinant of the effectiveness of HIV treatment programs is the capacity of sites to implement recommended services and identify systematic changes needed to ensure that invested resources translate into improved patient outcomes. We conducted a survey in 2014 of HIV care and treatment sites in the seven regions of the International epidemiologic Database to Evaluate AIDS (IeDEA) Consortium to evaluate facility characteristics, HIV prevention, care and treatment services provided, laboratory capacity, and trends in the comprehensiveness of care compared to data obtained in the 2009 baseline survey. Methods: Clinical staff from 262 treatment sites in 45 countries in IeDEA completed a site survey from September 2014 to January 2015, including Asia‐Pacific with Australia ( n  = 50), Latin America and the Caribbean ( n  = 11), North America ( n  = 45), Central Africa ( n  = 17), East Africa ( n  = 36), Southern Africa ( n  = 87), and West Africa ( n  = 16). For the 55 sites with complete data from both the 2009 and 2014 survey, we evaluated change in comprehensiveness of care. Results: The majority of the 262 sites (61%) offered seven essential services (ART adherence, nutritional support, PMTCT, CD4+ cell count testing, tuberculosis screening, HIV prevention, and outreach). Sites that were publicly funded (64%), cared for adults and children (68%), low or middle Human Development Index (HDI) rank (68%, 68%), and received PEPFAR support (71%) were most often fully comprehensive. CD4+ cell count testing was universally available (98%) but only 62% of clinics offered it onsite. Approximately two‐thirds (69%) of sites reported routine viral load testing (44–100%), with 39% having it onsite. Laboratory capacity to monitor antiretroviral‐related toxicity and diagnose opportunistic infections varied widely by testing modality and region. In the subgroup of 55 sites with two surveys, comprehensiveness of services provided significantly increased across all regions from 2009 to 2014 (5.7 to 6.5, p  < 0.001). Conclusions: The availability of viral load monitoring remains suboptimal and should be a focus for site capacity, particularly in East and Southern Africa, where the majority of those initiating on ART reside. However, the comprehensiveness of care provided increased over the past 5 years and was related to type of funding received (publicly funded and PEPFAR supported).